2015
DOI: 10.1371/journal.pone.0137506
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Internet Addiction among Internet Users: An Online Questionnaire Survey

Abstract: BackgroundsInternet addiction (IA) has become a major public health issue worldwide and is closely linked to psychiatric disorders and suicide. The present study aimed to investigate the prevalence of IA and its associated psychosocial and psychopathological determinants among internet users across different age groups.MethodsThe study was a cross-sectional survey initiated by the Taiwan Suicide Prevention Center. The participants were recruited from the general public who responded to the online questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
67
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(86 citation statements)
references
References 41 publications
10
67
1
8
Order By: Relevance
“…Neuroticism has been positively associated with (i) problematic internet use in all empirical research to date in correlational studies (e.g., [18][19][20]), (ii) comparison of groups of internet addicts and controls (e.g., [21,22]), and (iii) regression analyses (e.g., [23,19]). This association is also found in research assessing neuroticism by questionnaires based on (i) Eysenck's three-factor theory (e.g., [24][25][26][27][28][29][30][31][32][33]) and (ii) Zuckerman's five-factor model (e.g., [34]). Similarly, studies have also reported an association between low agreeableness and internet addiction (e.g., [21,23,18,20]) and low conscientiousness and internet addiction (e.g., [18,22,20]).…”
Section: Introductionsupporting
confidence: 56%
“…Neuroticism has been positively associated with (i) problematic internet use in all empirical research to date in correlational studies (e.g., [18][19][20]), (ii) comparison of groups of internet addicts and controls (e.g., [21,22]), and (iii) regression analyses (e.g., [23,19]). This association is also found in research assessing neuroticism by questionnaires based on (i) Eysenck's three-factor theory (e.g., [24][25][26][27][28][29][30][31][32][33]) and (ii) Zuckerman's five-factor model (e.g., [34]). Similarly, studies have also reported an association between low agreeableness and internet addiction (e.g., [21,23,18,20]) and low conscientiousness and internet addiction (e.g., [18,22,20]).…”
Section: Introductionsupporting
confidence: 56%
“…Availability of internet facility in portable devices like smart phones and tablets is one of the major contributing factor towards its excessive use. It has become an indispensable part of current modern living 4. The young generation has seen this facility from birth, is accustomed to its 24-hour access and cannot think of accomplishment of their daily tasks in its absence 5.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers found another criterion of internet addiction, as Wu, Lee, Liao, & Chang (2015) found the signs and symptoms include: a) use internet longer than intended, b) preoccupation with the internet, c) withdrawl symptoms when unable to access the internet, d) unsuccessful attempts to stop or reduce internet use, e) craving, f) loss of interest hobbies or activities ither than the internet, g) excessive internet use depite the knowledge of related problems, g) use of the internet to escape or relieve a negative mood, and h) lying about internet use. The types of activity involved IA include online gaming, social networking, online gambling, online shopping, virtual sex, and information overload (Wu, Lee, Liao, & Chang, 2015) According to previous research, Young (2004) found that Internet addiction has a negative impact in various aspects of social life.…”
Section: Introductionmentioning
confidence: 99%
“…The types of activity involved IA include online gaming, social networking, online gambling, online shopping, virtual sex, and information overload (Wu, Lee, Liao, & Chang, 2015) According to previous research, Young (2004) found that Internet addiction has a negative impact in various aspects of social life. One of them in the academic field.…”
Section: Introductionmentioning
confidence: 99%